Sono‐Triggered In Situ Vaccine via a Chlorin‐Based Small Molecule Sensitizer for Systemic Cancer Therapy - Jinrong Li; Kun Shao; Lin Cheng; Guanyi Zhang; Jianlong Su; Yiming Liu; Yang Wang; Chengdong Wang; Zhihao Wu; Xu Wang; Yuxuan Zhang; Bohua Yan; et al. (Angewandte Chemie International Edition, 2026)
ABSTRACT Unimolecule‐mediated sonodynamic therapy (SDT) offers a promising approach to combat tumors systemically by enabling synergistic sono‐triggered cytotoxicity and in situ vaccine‐like effects within tumors. Although chlorin‐based sensitizers have achieved clinical success in phototherapy, their translation to SDT has been impeded by inadequate ultrasound (US)‐triggered reactive oxygen species (ROS) generation, leading to suboptimal immunogenic cell death (ICD) and compromised antitumor immunity. To address this, we designed two organic sonosensitizers based on the natural product‐derived scaffold, Chenghai pyropheophorbide‐a (CHPpa). CHPpa‐er was constructed by appending a p ‐toluenesulfonamide group for specific endoplasmic reticulum (ER) targeting. Its analogue, CHPpa‐er‐Asp, was additionally functionalized with aspartic acid to modulate molecular polarity. Remarkably, despite differing by only one pharmacophore, the two compounds exhibited profoundly distinct profiles in target protein (K ATP channel) engagement and intracellular trafficking, highlighting the critical impact of rational molecular design. As the lead candidate, CHPpa‐er elicited precise, intraluminal ROS bursts under US, inducing severe ER stress and robust ICD. In two preclinical tumor models, CHPpa‐er‐mediated SDT effectively suppressed both primary tumor growth and metastasis by provoking potent systemic antitumor immunity. This work introduced a unimolecular sonosensitizer strategy that transformed SDT from a localized modality into a systemic intervention, offering a translatable platform for comprehensive cancer therapy.